Antiviral Therapy Improves Postoperative Survival in Patients With Hepatocellular Carcinoma. Issue 1 (January 2015) - Huang, Gang; Lau, Wan Yee; Wang, Zhen-Guang; Pan, Ze-Ya; Yuan, Sheng-Xian; Shen, Feng; Zhou, Wei-Ping; Wu, Meng-Chao
<x xml:space="preserve">Abstract</x> Objective: A randomized controlled trial was conducted to find out whether antiviral therapy in patients with hepatitis B–related hepatocellular carcinoma (HCC) improves long-term survival after hepatic resection. Background: Despite advances in surgery and in multidisciplinary treatment, there is still no effective adjuvant treatment to prevent HCC recurrence after R0 resection for HCC. Whether antiviral therapy is useful in reducing postoperative HCC recurrence is unclear. Methods: Between May 2007 and April 2008, patients who received R0 hepatic resection for HBV-related HCC were randomly assigned to receive no treatment (the control group, n = 100) or antiviral therapy (adefovir 10 mg/d, the antiviral group, n = 100). Results: The baseline clinical, laboratory, and tumor characteristics of the 2 groups were comparable. The 1-, 3-, and 5-year recurrence-free survival rates for the antiviral group and the control group were 85.0%, 50.3%, 46.1% and 84.0%, 37.9%, 27.1%, respectively. The corresponding overall survival rates for the 2 groups were 96.0%, 77.6%, 63.1% and 94.0%, 67.4%, 41.5%, respectively. The recurrence-free survival and overall survival for the antiviral group were significantly better than the control group (P = 0.026, P = 0.001). After adjusting for the confounding prognostic factors in a Cox model, the relative risks of recurrence and death for antiviral treatment were 0.651 [95% confidence interval (CI): 0.451–0.938; P = 0.021] and 0.420 (95% CI: 0.271–0.651; P < 0.001). Antiviral therapy was an independent protective factor of late tumor recurrence (HR = 0.348, 95% CI: 0.177–0.687; P = 0.002) but not of early tumor recurrence [hazard ratio (HR) = 0.949, 95% CI: 0.617–1.459; P = 0.810]. Conclusions: In patients with hepatitis B–related HCC, adefovir antiviral therapy reduced late HCC recurrence and significantly improved overall survival after R0 hepatic resection.